PEMANFAATAN SMART APP CREATOR UNTUK MENDUKUNG LITERASI DIGITAL SISWA KELAS VI SD - Fatma Nurmala, Asih; Fitrotun Nisa, Ana; Maria Zulfiati, Heri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the use of Smart App Creator to support digital literacy for sixth grade elementary school students. The method used is descriptive qualitative. Data collection techniques use interview questionnaires and documentation. This research produces Android-based interactive learning media, namely Smart App Creator, on solar system material. The research subjects were 9 grade 6th students at JL State Elementary School, consisting of 4 male students and 5 female students. The data analysis technique uses stages of data reduction, data presentation, and drawing conclusions. The research results show that the use of Smart App Creator supports the digital literacy of sixth grade elementary school students. Students who use the Smart App Creator learning media also feel happy because they are able to use interactive Android-based applications used on their smartphones. Students become more enthusiastic and active in learning and support digital literacy activities in learning. The use of Smart App Creator in supporting digital literacy activities for sixth grade elementary school students has a positive impact because it can increase enthusiasm for learning so that researchers recommend teachers or other researchers to use or adopt and perfect this learning media.